Les travaux du groupe du CIPEA sur l'agrostologie dans le rift de l'Ethiopie - Russell-Smith, A. (1983)
Discusses briefly the work of ILCA's Forage Legume Agronomy Group in the Ethiopian Rift Valley. Presents and discusses the performance of 10 promising forage legumes in initial evaluation trials at Abernossa ranch; includes species of Stylosanthes, Centrosema, Desmodium, Lablab, Medicago, Leucaena and Lotononis.